Oral and nasal mucosal pathways of prion infection in chronic wasting disease - Denkers, Nathaniel David, author; Hoover, Edward Arthur, 1942-, advisor; Zabel, Mark Douglas, committee member; Suchman, Erica, committee member; Ross, Eric D., committee member (Colorado State University. Libraries, 2010)
Chronic wasting disease (CWD) is a fatal neurodegenerative prion disease of deer, elk, and moose. The unique feature of CWD as a prion disease is its efficient transmission among cervids in nature. As with other prion infections, CWD disease inception relies on the conversion of the normal host cellular prion protein (PrPC) to the abnormal, protease-resistant isoform (PrPCWD)--the diagnostic hallmark of prion diseases. Since its detection in Colorado in 1967, CWD has spread to captive and free-ranging cervid species in 16 additional states, 3 Canadian provinces, and one Asian country. CWD is also exceptional as the only prion disease to afflict a free-ranging, wildlife population. Understanding the facile means by which CWD is transmitted from animal to animal is important not only in understanding prion transmission overall but also in elucidating the potential public health consequences of cross species prion transmission. This dissertation work asks whether and how CWD prions are able to cross the oral and nasal mucosa to induce infection and disease. The above questions were addressed through the use of two strains of transgenic mice that express the normal cervid prion protein [Tg(CerPrP)1536, Tg(CerPrP-E226)5037+/-] and prion protein knockout mice [FVB PrP0/0] exposed by either aerosol, nasal, or oral route to CWD prions. In the first series of studies, cohorts of Tg(CerPrP)1536 mice were exposed to brain homogenates from either CWD-infected or CWD-naïve deer via either aerosolization or direct nasal installation. In the second series of studies, cohorts of Tg(CerPrP-E226)5037+/- mice were exposed to the same inocula via installation onto the lingual mucosal surface which had or had not been previously subjected to superficial abrasions. Mice were then observed and tissues from each cohort, at time points ranging from weeks to as long as 2 years post inoculation, were examined for the presence of the abnormal prion protein of CWD (PrPCWD) using western blotting and immunohistochemistry assays. The final studies employed the same inoculation techniques used in the first two studies to seek to identify early (less than 4 hours) sites of prion entry via the mucous membranes. The results of these dissertation studies demonstrated; 1) that CWD could be transmitted by aerosol exposure with high efficiency compared with direct inoculation onto the nasal mucosa; and 2) that micro-abrasions to the lingual surface greatly facilitated CWD prion transmission. Finally and perhaps surprisingly, we were unable to detect PrPCWD in either the nasal or oral mucosa shortly after inoculation or at any time, even after the onset of clinical symptoms of CWD. The results from these studies suggest that; 1) CWD prions can be transmitted by aerosol exposure; thus exposure to the respiratory system merits increased consideration in prion transmission and biosafety; 2) minor oral mucosal injury does greatly facilitate prion infection--a potentially significant co-factor in CWD transmission of foraging cervids; and 3) these mucosal pathways may explain how and why CWD is transmitted with high efficiency in animals exposed to low concentrations of prions in nature.
Keywords: prion; oral mucosa; nasal mucosa; CWD; chronic wasting disease; aerosol; Prion diseases in animals -- Transmission; Chronic wasting disease -- Transmission; Airborne infection; Communicable diseases -- Transmission; Cervidae -- Diseases -- Transmission